1995
DOI: 10.1577/1548-8659(1995)124<0016:tasvif>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variation in Fecundity of Yellowtail Rockfish

Abstract: Fecundities of the commercially important yellowtail rockfish Sebastes flavidus were compared to determine interannual variability and geographic variation, which will assist in stock assessment, characterization, and management. Gravimetrically estimated fecundities were compared in 1985–1991 between California, the southern extent of the speciesˈ distribution, and coastal waters of Washington, near the center of the speciesˈ abundance, where yellowtail rockfish are most heavily fished. California yellowtail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The age of 50% maturity is variable among species but is typically 5-7 years, and may be as late as 20 years in some species (Wyllie Echeverría 1987;Barss 1989;Love et al 1990;O'Connell and Fujioka 1991). Several studies have shown geographical variation in age-at-maturity depending on latitude and depth (Gunderson et al 1980;Pearson and Hightower 1991;Eldridge and Jarvis 1994;Gunderson 1996). Many species have sex-specific growth rates, which can result in differential age-at-maturity and sex-specific natural mortality rates (Love et al 1990; Lenarz and Wyllie Echeverría 1991).…”
Section: B Backgroundmentioning
confidence: 99%
“…The age of 50% maturity is variable among species but is typically 5-7 years, and may be as late as 20 years in some species (Wyllie Echeverría 1987;Barss 1989;Love et al 1990;O'Connell and Fujioka 1991). Several studies have shown geographical variation in age-at-maturity depending on latitude and depth (Gunderson et al 1980;Pearson and Hightower 1991;Eldridge and Jarvis 1994;Gunderson 1996). Many species have sex-specific growth rates, which can result in differential age-at-maturity and sex-specific natural mortality rates (Love et al 1990; Lenarz and Wyllie Echeverría 1991).…”
Section: B Backgroundmentioning
confidence: 99%
“…Accurate fecundity estimates are important for understanding dynamics of fish populations, predicting trends in population abundance, and estimating spawning-stock biomass (Eldridge and Jarvis 1995). Reproductive potential influences the ability of a species to respond to abiotic and/or biotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the reproductive biology of fishes is critical for understanding a species' life history and devising appropriate management strategies [1,2]. Studies in reproductive biology mainly focus on sex ratio, spawning time, gonad development, length at maturity, and fecundity.…”
Section: Introductionmentioning
confidence: 99%